Strategi Pembinaan Keagamaan Muallaf Dayak Meratus Kalimantan Selatan - Nadzmi Akbar Baderun; Samsul Rani (Alhadharah: Jurnal Ilmu Dakwah, 2021)
Abstract A person becomes a Muslim convert because he believes in Islamic teachings' goodness, benefits, and truth. On the other hand, converts of Dayak Meratus generally still have many shortcomings and problems carrying out their new religion. Thus, the guidance of Dayak Meratus converts must be carried out by Muslims. It is still unclear that the guidance carried out for Dayak Meratus converts raises how the basic strategy for cultivating Dayak Meratus converts in South Kalimantan is necessary. Religion, supporting and inhibiting factors for converting. Data collection was carried out by observing, interviewing, and opening up documents that could present facts and events in the field. The interactive analysis process is in the following order: data collection, data condensation, data modeling, and describing and verifying conclusions. This research found that the convergence coaching program was made in detail by coaches who were in the field to suit field conditions. Dayak Meratus converts' religious guidance is carried out by using a family approach, warmth, meeting intensity or always being close to converts, teaching the practice of worship, muamalah, and instilling faith. The inhibiting factors for conversion are; lack of dai, converts are scattered over a wide area, it is challenging to gather at one place, the busyness of converts who make a living to a remote area.